2021
DOI: 10.1002/adfm.202106876
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Sinter‐Resistance and Catalyst Accessibility in Raspberry‐Colloid‐Templated Catalyst Design

Abstract: Nanoparticle (NP) sintering is a major cause of the deactivation of supported catalysts. Raspberry-colloid-templated (RCT) catalysts are an emerging class of materials that show an unprecedented level of sinter-resistance and exhibit high catalytic activity. Here a comprehensive study of the origin of NP stability and accessibility in RCT catalysts using theoretical modeling, 3D electron microscopy, and epitaxial overgrowth is reported. The approach is showcased for silica-based RCT catalysts containing dilute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…The number of CO 2 molecules is related to the amount of surface oxygen species, which in turn relates to the Pd content (see the Experimental Section and Supporting Information for details). Following this method, surface Pd contents of 1.12 ± 0.67, 6.78 ± 1.36, and 12.65 ± 1.41% were calculated for Pd 8 Au 92 , Pd 10 Au 90 , and Pd 13 Au 78 , respectively, assuming a degree of nanoparticle embedding in the support of 85% in the RCT catalysts 14 (Figure 2). Note that this method only counts the contiguous Pd atoms and neglects the isolated Pd single atoms since isolated Pd is unable to dissociate molecular oxygen.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The number of CO 2 molecules is related to the amount of surface oxygen species, which in turn relates to the Pd content (see the Experimental Section and Supporting Information for details). Following this method, surface Pd contents of 1.12 ± 0.67, 6.78 ± 1.36, and 12.65 ± 1.41% were calculated for Pd 8 Au 92 , Pd 10 Au 90 , and Pd 13 Au 78 , respectively, assuming a degree of nanoparticle embedding in the support of 85% in the RCT catalysts 14 (Figure 2). Note that this method only counts the contiguous Pd atoms and neglects the isolated Pd single atoms since isolated Pd is unable to dissociate molecular oxygen.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The incorporation of PdAu particles in RCT-SiO2 has been reported in previous publications and does not depend on the concentration of Pd. 16 It is known that a silica layer around the particles will lead to their deactivation as it occludes the metal/gas interface. However, it cannot explain the differences in conversion rates observed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…10,11,12,13,14 This synthesis approach improves the stability of the nanoparticles at elevated temperatures by preventing particle migration and coalescence (PMC) and substantial changes in morphology during pre-treatment. 10,15,16 Prior studies have also shown that the highest rate for 1-hexyne conversion was achieved with Pd0.04Au0.96 particles. 17,4 In contrast, Pd0.02Au0.98 and Pd0.09Au0.91 were less efficient, as the conversion for 1-hexyne per atom of Pd was lower than Pd0.04Au0.96.…”
Section: Toc Introductionmentioning
confidence: 97%
“…However, especially for catalytic applications this may be deliberately used to form undercoordinated and therefore reactive sites. For example, embedding of separated nanoparticles into a solid support can effectively suppress sintering effects. Combining such methods with the presented on-particle ligand synthesis may represent a new approach to fabricate catalyst for ligand-directed catalysis with improved selectivity. …”
Section: Discussionmentioning
confidence: 99%